Argentina : Overview of Tobacco Use, Tobacco Control Legislation, and Taxation - World Bank Group (World Bank, Washington, DC, 2019)
This country brief provides an overview of tobacco legislation, use, and taxation in Argentina. Argentina is the only country in Latin America which did not become a Party to the WHO Framework Convention on Tobacco Control (FCTC). Still, many of the FCTC provisions are included in the legislation. The prevalence of smoking was quite high in 1970-1990s ranging between 40-58 percent among men and 20- 25 percent among women. After tobacco control measures were implemented, the prevalence of smoking decreased. Tobacco consumption and smoking prevalence in Argentina decreased due to the implementation of comprehensive tobacco control policies and some economic factors, which reduced cigarette affordability in the country. In Argentina, cigarette affordability and tobacco consumption reduction were observed in: (1) 1999-2002; (2) 2014-2015; (3) 2016. In the first case (1999-2002), it was mainly caused by the reduction in population income during the economic recession. In 2014-2015, tax rates were not changed, and the main factor of the affordability reduction was the pricing policy of the tobacco industry. The largest decline in affordability was achieved by the government taxation policy implemented in May 2016: the effective excise tax rate was actually increased by about 100. Cigarette sales in 2016 declined by 5 billion sticks or by 12 percent. Tobacco taxation system should be simplified to one excise tax with a unified ad valorem rate for all tobacco products and specific minimum excise rates for each tobacco product. The specific tax rates should be set high enough to prevent the sales of very cheap tobacco products, and these specific rates should be annually increased above the inflation rate to ensure both the reduction of tobacco consumption and the increase of governmental revenue. Subsidies for tobacco growers through the Special Tobacco Fund are counterproductive from both public health and economic perspectives. Tobacco use surveillance and monitoring should be further developed in Argentina, including regular surveys with a collection of comprehensive information on tobacco products consumed in the country.